2016
DOI: 10.1039/c6ra15060h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of B2O3addition on optical and structural properties of TiO2as a new blocking layer for multiple dye sensitive solar cell application (DSSC)

Abstract: International audience

TiO2–B2O3 sol–gel films were prepared using titanium(IV) isopropoxide as a Ti source and boric acid (H3BO3) as B precursor. B2O3 doping was found to improve the characteristics of TiO2 films making them suitable to use as blocking TiO2 layers in DSSC B2O3 acted as a flux and glass forming oxide leading to amorphous vitreous layers having an average thickness of 50 nm. Films were transparent, adherent and perfectly continuous without any leakage current. X-ray diffraction measurements p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Whereas, a high peak of rutile phase (110) was located at 2θ = 27.49° ( Figure 7 and Figure 8 ). It was reported that crystallinity of TiO 2 was decreased with the addition of boron content [ 52 ]. This work also showed that the intensity of TiO 2 was decreased when added with B 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, a high peak of rutile phase (110) was located at 2θ = 27.49° ( Figure 7 and Figure 8 ). It was reported that crystallinity of TiO 2 was decreased with the addition of boron content [ 52 ]. This work also showed that the intensity of TiO 2 was decreased when added with B 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…1, a II substrate), which is represented by a halo at 2Ө ~ 20°. According to [55], this broad peak is assigned to weakly ordered anatase. Peaks of H 3 BO 3 are also present [56,57].…”
Section: Products Of Ablation On Substratementioning
confidence: 99%
“…The diffraction pattern of the film deposited on the substrate (Figure 1c) is represented mainly by the halo (amorphous phase) and weak peaks related to TiO 2 in the form of rutile and anatase [21]. The complex halo can be considered as a superposition halo from anatase titanium oxide phase containing B 2 O 3 [22] and glass-like B 2 O 3 [23].…”
Section: Tib +O Tio +B O → (3)mentioning
confidence: 99%